Positive margins and plexitis increase the risk of recurrence after ileocecal resection: A systematic review and meta-analysis - Yzet, Clara; Riault, Clémentine; Brazier, Franck; Grados, Lucien; Nguyen-Khac, Eric; Chatelain, Denis; Sabbagh, Charles; Buisson, Anthony; Diouf, Momar; Fumery, Mathurin (Digestive and Liver Disease, 2023)
There is debate over the impact of residual microscopic disease after ileocecal resection in Crohn's disease (CD) to predict recurrence. We conducted a meta-analysis to evaluate the impact of positive histological margins and plexitis after ileocecal resection on the risk of postoperative recurrence. Using a systematic search, we identified. 30 studies evaluating the impact of inflammatory margins on CD recurrence. The primary outcome was the postoperative clinical recurrence and secondary outcomes were surgical, and endoscopic recurrence. We performed random-effects meta-analysis and estimated odds ratio (OR) and 95% CIs. Thirty studies were analyzed, seven focused on myenteric plexitis, six on submucosal plexitis and twenty-three on positive margins. Inflammatory margins were associated with a higher rate of clinical and surgical recurrences: respectively 14 studies - OR 2.38; 95% CI, 1.54 - 3.68- I2 = 68.2%, Q test-p = 0.0003 and 8 studies - OR, 1.52; 95% CI, 1.07–2.16 - I2 =0%; Q test-p = 0.43. The presence of myenteric plexitis was associated with a higher rate of clinical recurrence (4 studies- OR, 1.60; 95%CI, 1.12–2.29; I2= 0%, Q-test-p = 0.61), and of endoscopic recurrence (4 studies - OR, 4.25; 95%CI; 2.06–8.76; I2= 0%, Q test-p = 0.97). Submucosal plexitis was not associated with an increased risk of endoscopic recurrence (4 studies - OR, 0.94; 95%CI; 0.58–1.52; I2= 0%, Q test-p = 0.79). Inflammatory margins and/or plexitis were associated with postoperative recurrence after ileocecal resection for CD. These elements should be taken into account in future algorithm for prevention of postoperative recurrence.